Pedagogic manifiest. Pedagogy of the eternal recurrence: critisism to a pseudocrisis of the education, without educators” (Peru XXth and XXIth centuries) - Toledo Gutiérrez, Carlos (2014)
The educative reality and the national magisterial situation. Characteristics and problems in a nietzschean interpretation where it is claimed the existence of the nihilism in great part of the teachers, who live diary situations of professional frustration about the scarce cognitive achievements of their students. The crisis comes from the professor that self-identifies as a “specialist in teaching courses”. The possibility of personal and professional overcoming is found at the practice of “eternal recurrence” to the vocation. A quest for creative professional development in a permanent innovative attitude founded in the affirmation of identity as an educator and the will of power in the task of integral formation of the student.